2019
DOI: 10.1158/1538-7445.am2019-2838
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2838: The gut microbiome (GM) and immunotherapy response are influenced by host lifestyle factors

Abstract: Background: There is a growing appreciation for the GM in response to melanoma therapy. Recent work identified a favorable (T1) GM signature associated with checkpoint benefit. However, little is known about how lifestyle factors may influence features of the GM or about the influence of the GM on therapeutic outcomes to other common melanoma therapies. Methods: We prospectively collected fecal samples melanoma patients at MD Anderson Cancer Center and characterized the GM via 16S rRNA sequencin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(26 citation statements)
references
References 0 publications
0
23
0
3
Order By: Relevance
“…[286][287][288][289] Numerous environmental factors, including diet, medications, surgery, smoking, and physical activity, affect the composition of the microbiome, which provides both research challenges and opportunities. [290][291][292] • Explore microbiome-mediated mechanisms of oncogenesis and tumor suppression, including the consequences of a given microorganism on tumor growth, metastasis, and response to therapy. • Define mechanisms used by the human microbiota to control local and systemic immunity.…”
Section: Microbiomementioning
confidence: 99%
“…[286][287][288][289] Numerous environmental factors, including diet, medications, surgery, smoking, and physical activity, affect the composition of the microbiome, which provides both research challenges and opportunities. [290][291][292] • Explore microbiome-mediated mechanisms of oncogenesis and tumor suppression, including the consequences of a given microorganism on tumor growth, metastasis, and response to therapy. • Define mechanisms used by the human microbiota to control local and systemic immunity.…”
Section: Microbiomementioning
confidence: 99%
“…A very recent preliminary study, however, suggests that the intake of probiotic supplements in melanoma patients lowers the response to anti-PD1 immunotherapy by 70%, likely decreasing gut microbiota diversity (37). These controversial findings, which stand in conflict with the general perception of probiotics being beneficial and with previous results, deserve further investigations.…”
Section: Probiotics and Anticancer Therapies' Effectivenessmentioning
confidence: 84%
“…Probiotic use after ATBs could have opposite effect and delay restoration of the gut microbiota (81). One study focused on melanoma patients reported that the effect of immunotherapy might be negatively influenced by probiotics (82). Thus, it is necessary to find out the relation and inner mechanism between probiotics and the effect of ICIs in other kind of tumors.…”
Section: Ongoing Clinical Trials Of Gut Microbiota In Icismentioning
confidence: 99%